The amount of liquid patients use to take tablets or capsules - Fuchs J (Centro de Investigaciones y Publicaciones Farmaceuticas, 2009)
The correct use of pharmaceutical drugs supports therapy success and reduces the number of adverse side effects. One relevant aspect of use concerns the amount of liquid consumed when taking compact and shaped medicines. Objective: The aim of this study was to investigate the volume of liquid used by patients when administering their medication.Methods: Every patient who bought tablets or capsules from the study leader in a pharmacy in Jena (Germany), and wanted to take their medicine immediately, received a glass containing 150ml of water. The volume of water consumed by the patients was measured after they took their medication. Results: 21 out of the 136 participants (15.4%) used only up to 60ml of liquid to take their tablets or capsules. Significant influences of demographic aspects, such as age or gender, on the volume of used liquid were not found. However, an increase in tablet or capsule size led to a significant increase in the volume of swallowed liquid.Conclusion: Patients need to be better informed about drinking a sufficient amount of liquid when taking tablets or capsules orally. Therefore, it is important that every package insert of compact and shaped medicines contains this information. In addition, medical and pharmaceutical experts should also provide this advice to their patients.